A Strategıc Framework for Good Governance through E-Governance ın Kathmandu, Nepal - Dhruba Lal Pandey, PhD, Nischal Risal, Mphil (International Journal of Advanced Science and Technology, 2020)
The study aims to assess the level and use of e-services and examine the impact of social, economical and political governance on e-governance. The study has incorporated e-governance practice as dependent variable which is explained by the level of corruption, the level of inefficiency, the level of harassment and the level of difficulty encountered. The social, economical and political governance have been considered as independent variables in the study. The e-citizen, e-society and e-administration have been considered as moderating variables in the study. The study has adopted the descriptive and correlational research design. All concerned persons related to ministries, universities, business organizations and government offices are considered as population of the study. The sample size has been confined to 393. The purposive and convenience sampling technique have been used to select the sample. The statistical measure mean has been used to assess the position of dependent, independent and moderating variables. The correlation test has been run to know the association between the dependent and independent variables. The impact of independent variables of the dependent variables has been assessed through ordinary least square (OLS) regression model. The results of the study have shown that the good governance practices have been used but not satisfactory in the view of educated and experienced people. The lack of infrastructures: quality manpower, computer knowledge and language have been found as the major challenges to implement e-governance practices in Nepal. The study concluded that the improvement in political policies and social domains, e-governance can be effective but cost and other economic indicators are to be improved negatively so as to improve in e-governance practices.